1994
DOI: 10.1029/94jc01382
|View full text |Cite
|
Sign up to set email alerts
|

A southern hemisphere verification for the TOPEX/POSEIDON satellite altimeter mission

Abstract: As a check on the total system accuracy of the TOPEX/POSEIDON satellite, a southern hemisphere verification study was undertaken in Bass Strait (41°S) immediately adjacent to the Southern Ocean. An acoustic tide gauge and two pressure gauges were installed on the southern side of Bass Strait near where descending pass 88 crosses the Tasmanian coast. The tide gauge benchmark height was estimated relative to the laser tracking station at Orroral Valley and the very long baseline interferometry station near Hobar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Data from dedicated Jason calibration sites at Corsica (Bonnefond et al 2003) and Bass Strait (Watson et al 2003) showed similar behavior. Ironically, these initial estimates of the Jason-1 SSH bias nearly matched early estimates of the TOPEX SSH bias Born et al 1994;Ménard et al 1994;White et al 1994). More contemporary estimates of the Jason-1 SSH bias are roughly 40 mm smaller (e.g., Willis 2009;Bonnefond et al 2010), owing primarily to evolutions in the altimetric data products.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Data from dedicated Jason calibration sites at Corsica (Bonnefond et al 2003) and Bass Strait (Watson et al 2003) showed similar behavior. Ironically, these initial estimates of the Jason-1 SSH bias nearly matched early estimates of the TOPEX SSH bias Born et al 1994;Ménard et al 1994;White et al 1994). More contemporary estimates of the Jason-1 SSH bias are roughly 40 mm smaller (e.g., Willis 2009;Bonnefond et al 2010), owing primarily to evolutions in the altimetric data products.…”
Section: Introductionmentioning
confidence: 60%
“…With data from additional overflights and improved GPS-based determinations of the platform geocentric height and velocity, Haines et al (1996) reported a TOPEX bias of 125 ± 20 mm at the conclusion of the three-year primary mission. Also identified in early results from other dedicated calibration sites (Ménard et al 1994;White et al 1994;Murphy et al 1996), the bias was determined to be the expression of an error in the software used to produce the TOPEX data for the mission scientists. (O. Zanife, P. Vincent, and P. Escudier of CNES are credited with discovering the software error.)…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have compared tidally corrected SSH data with tide gauge records [e.g., Mitchum , 1994; Nerem et al ,1994; Le Provost , 1994; Koblinsky , 1999]. Actual calibration studies [ Born et al , 1994; Christensen et al , 1994; Ménard et al , 1994; White et al , 1996; Exertier et al , 2000] seek to compare absolute levels from TOPEX at, or carefully extrapolated to, the calibration site, and have demonstrated RMS differences ranging from to about 1.5 to 3.5 cm. Studies using non‐coincident coastal and island tide gauges, pressure gauges or inverted echosounders, and dynamic heights computed from temperature sensors [ Katz et al , 1995; Mitchum , 1994; Picaut et al , 1995; Verstraete and Park , 1995; Woodworth et al , 1996; Murphy et al , 1996] generally achieve RMS differences ranging between about 4 and 12 cm, depending upon location, with correlations ranging from 0.4 to 0.9, but typically 0.6 to 0.7.…”
Section: Discussionmentioning
confidence: 99%
“…It must be emphasised that the consortium already has an excellent working relationship, as evidenced by joint publications (eg. Ananga et al, 1995;King et al, 2000;Morgan et al, 1996;Phillips et al, 1998;Tregoning et al, 1998a;White et al, 1994), a number of collaborative grants supported by the Australian Research Council (eg. Featherstone and Rizos 1997 RIEFP grant;Morgan, Coleman and Rizos 1993 large grant;Coleman and Morgan 1998 large grant), as well as other informal collaborative projects.…”
Section: The Consortiummentioning
confidence: 99%